Cranial biomechanics in basal urodeles: the Siberian salamander (Salamandrella keyserlingii) and its evolutionary and developmental implications - Zhou, Zupeng (Sci Rep, 2017)
Developmental changes in salamander skulls, before and after metamorphosis, affect the feeding capabilities of these animals. How changes in cranial morphology and tissue properties affect the function of the skull are key to decipher the early evolutionary history of the crown-group of salamanders. Here, 3D cranial biomechanics of the adult Salamandrella keyserlingii were analyzed under different tissue properties and ossification sequences of the cranial skeleton. This helped unravel that: (a) Mechanical properties of tissues (as bone, cartilage or connective tissue) imply a consensus between the stiffness required to perform a function versus the fixation (and displacement) required with the surrounding skeletal elements. (b) Changes on the ossification pattern, producing fontanelles as a result of bone loss or failure to ossify, represent a trend toward simplification potentially helping to distribute stress through the skull, but may also imply a major destabilization of the skull. (c) Bone loss may be originated due to biomechanical optimization and potential reduction of developmental costs. (d) Hynobiids are excellent models for biomechanical reconstruction of extinct early urodeles.